Field Research in Political Science : Practices and Principles - Kapiszewski, Diana; MacLean, Lauren M.; Read, Benjamin L. (Cambridge : Cambridge University Press, 2015)
Field research - leaving one's home institution in order to acquire data, information or insights that significantly inform one's research - remains indispensable, even in a digitally networked era. This book, the first of its kind in political science, reconsiders the design and execution of field research and explores its role in producing knowledge. First, it offers an empirical overview of fieldwork in the discipline based on a large-scale survey and extensive interviews. Good fieldwork takes diverse forms yet follows a set of common practices and principles. Second, the book demonstrates the analytic benefits of fieldwork, showing how it contributes to our understanding of politics. Finally, it provides intellectual and practical guidance, with chapters on preparing for field research, operating in the field and making analytic progress while collecting data, and on data collection techniques including archival research, interviewing, ethnography and participant observation, surveys, and field experiments.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).